(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In the paper, the authors present and explain their conducted research on the origin of Lujza St. Jakšić, a teacher at the Higher School for Girls in Belgrade and the author of the first English grammar book in Serbian. The genealogical research was sparked by one particular detail from literature – Letters from Salonika by Jelena Dimitrijević, to be exact. The research was carried out in several gradually described phases, pointing to numerous incongruences of the biographical data within the corpus of sources and documents that were searched. Even though the presented research is not placed within the horizon of final answers and solutions, the authors explain the epistemic value of the personal document, the significance of digital content and the scientific relevance of similar research in the context of humanities.